Canine vector-borne parasites in the Galapagos - Carla Andreea Culda; Nathalie G. Tejena Rodriguez; Fortunato Puleo; Rafael M. Polit Sosa; Luciana Cătălina Panait; Cristina Daniela Cazan; Georgiana Deak; Renato Leon; Rommel Lenin Vinueza; Diego Páez-Rosas; Andrei Daniel Mihalca (Parasites & Vectors)
Abstract Background The extraordinary Galapagos Islands, with an impressive number of endemic and native species, maintain the interest and curiosity for researchers from all over the world. The native species are known to be vulnerable to new pathogens, cointroduced with their invasive hosts. In the case of invasive parasitic arthropods, their evolutionary success is related to the association with other invasive hosts (such as domestic animals). These associations could become a significant driver of change, as occasionally they can seek another hosts and have the capacity to transmit pathogens between domestic and wild animals. The current study aims to identify the distribution and abundance of canine vector-borne parasites in the Galapagos Islands based on the possibility that some of them could spill over to endemic mammals. Methods A total of 1221 blood samples were randomly collected from privately owned dogs on San Cristóbal, Isabela, Santa Cruz, and Floreana Islands during the years 2021 and 2022. All samples were examined for vector-borne pathogens using the modified Knott’s test and conventional, nested, and multiplex polymerase chain reactions (PCRs), followed by sequencing. Results The PCR and Knott tests confirmed the presence of Dirofilaria immitis (2%, 25/1221) in all islands. While molecular analyses showed heartworm DNA only in dogs from the San Cristóbal (3.3%) and Isabela (2.4%) Islands. Moreover, other pathogens Babesia vogeli (3%, 37/1221) and Hepatozoon canis (0.2%, 2/1221) were detected for the first time by molecular analyses. Conclusions Dogs from Galapagos are hosts to various pathogens, of which some are potentially zoonotic while some other could be spill-over to endemic endangered carnivores, such as sea lions. To understand and limit their impact, long-term surveillance, control, and awareness is needed. Graphical abstract